Geological and tourist attractions of southern Bornholm - Jamorska, Izabela; Gil, Katarzyna; Kamińska, Anna; Piątkowska, Daria; Sokólska, Anna; Żarnowska, Joanna (Geotourism/Geoturystyka, 2015)
The following article presents the description of seven geological and tourist routes in the southern part of the Danish island called Bornholm. The fi eldwork, which took place during the expedition of the Geography Students’ Scientifi c Group from the Faculty of Earth Sciences, Nicolaus Copernicus University in Toruń, included photographic documentation and the location of rock concentrations by means of a GPS receiver. The researched routes reveal both geological diversity of the island – Precambrian, Palaeozoic, and Mesozoic rocks, as well as tourist sites, such as round churches, historical windmills, rune stones and numerous attractions of major cities of the island.